Bureaucracy, collegiality and social change : redefining organizations and multilevel relational infrastructures - Lazega, Emmanuel, 1956- (Social networks, organizations and markets, 2020)
"This insightful book theorizes the contrast between two logics of organization: bureaucracy and collegiality. Based on this theory and employing a new methodology to transform our sociological understanding, Emmanuel Lazega sheds light on complex organizational phenomena that impact markets, political economy, and social stratification. Lazega focuses on how organizations use and combine logics of bureaucracy and collegiality, deploying and developing the analysis of multilevel networks to explore how these logics coalesce and interact in organizational settings and stratigraphies. Revisiting sociological knowledge on various phenomena, such as coopetition in science, markets and government, the creation of new institutions in political economy and elite self-segregation, this book advances our perception of the changes introduced in the contemporary 'science of organizations' by the digitalization of society. Offering new theoretical insights into organizations, this book is crucial for sociologists of organizations and management scholars, as well as postgraduate students, in search of an innovative understanding of the trajectories of contemporary organizations. The analysis of multilevel networks will also benefit practitioners and analysts working in the field"--